Field test of earth pressure at pile-soil interface by single pile penetration in silty soil and silty clay. Issue 145 (June 2021) - Wang, Yonghong; Sang, Songkui; Zhang, Mingyi; Liu, Xueying; Yang, Suchun
Abstract: Prestressed high-strength concrete (PHC) pipe pile with static press-in method is widely used in recent years. The earth pressure at the pile-soil interface caused by the process of pile jacking has an important influence on the jacked pile construction and even the bearing characteristics. Based on a construction project in Dongying, the change law of earth pressure at pile-soil interface caused by the penetration of PHC pipe pile is analyzed by monitoring the earth pressure at pile-soil interface during pile jacking, and the evolution characteristics of earth pressure at pile-soil interface in viscous soil foundation are revealed. The results show that the earth pressure at the pile-soil interface at different positions (h/B) caused by the penetration of PHC pipe pile gradually increases with time. In the process of pile jacking, the influence of pile jacking on the earth pressure at the pile-soil interface on the pile body and part that exceeds the relative distance of effective pile end (h/B) is weak. In the process of pile jacking, the earth pressure at the pile-soil interface is greatly affected by the relative height of the pile end (h/B), so it is necessary to consider the effect of the pile length to calculate the earth pressure at the pile-soil interface. The phenomenon of "lateral pressure degradation" exists with the increase of h/B in the earth pressure at the pile-soil interface. The research results have certain engineering guiding significance for construction and bearing capacity determination of jacked pile in viscous soil foundation. Highlights: The change law of earth pressure caused by penetration of PHC pipe pile is analyzed. The evolution characteristics of earth pressure at pile-soil interface in viscous soil foundation are revealed. The research results have certain engineering guiding significance for construction and bearing capacity.